75 Informing unintentional drowning prevention in Indonesia: Global Burden of Disease 2019 Study. (20th November 2022) - Cenderadewi, Muthia; Franklin, Richard; Devine, Susan
Abstract : Background: High fatalities of unintentional drowning have been reported in low and middle-income countries. However, little is known about unintentional drowning prevention in Indonesia. Objective: To examine mortality rates and risk factors of unintentional drowning in Indonesia to inform drowning prevention. Methods: This total population retrospective cohort study analysed quantitative unintentional drowning data sourced from The Global Burden of Disease (GBD) 2019 study by The Institute for Health Metrics and Evaluation, to generate estimates of mortality rates by gender, age group, and province within Indonesia, informing gaps of knowledge for evidence-based policy development in Indonesia. Results: A decline in unintentional drowning mortality rates was observed, with an average annual mortality of 2.58/100, 000. Males were 1.81 (95% CI: 1.79 - 1.84) times more likely than females to unintentionally drown. Average annual mortality rate was highest amongst the under 5 age group (9.67/100, 000) and over 70's (5.71/100, 000 for males; 5.14/100, 000 for females). Distributions of drowning deaths vary depending on region with mortality higher in Kalimantan and Papua. Conclusion: There has been a downward trend in number and rate of drowning deaths in Indonesia from 2005 onwards. Being male, aged under 5 and over 70, and residing in provinces such as Kalimantan and Papua were recognised risk factors. The findings highlight the importance of enhancing drowning data collection systems, as well as identifying drowning risk factors, to inform drowning preventive strategies in Indonesia. Learning outcome: Participants will be able to analyse gaps of knowledge for evidence-based drowning prevention policy development in Indonesia.